Improved loss-of-function CRISPR-Cas9 genome editing in human cells concomitant with inhibition of TGF-β signaling - Tarun Mishra; Vipin Bhardwaj; Neha Ahuja; Pallavi Gadgil; Pavitra Ramdas; Sanjeev Shukla; Ajit Chande (Elsevier, 2022)
Strategies to modulate cellular DNA repair pathways hold immense potential to enhance the efficiency of CRISPR-Cas9 genome editing platform. In the absence of a repair template, CRISPR-Cas9-induced DNA double-strand breaks are repaired by the endogenous cellular DNA repair pathways to generate loss-of-function edits. Here, we describe a reporter-based assay for expeditious measurement of loss-of-function editing by CRISPR-Cas9. An unbiased chemical screen performed using this assay enabled the identification of small molecules that promote loss-of-function editing. Iterative rounds of screens reveal Repsox, a TGF-β signaling inhibitor, as a CRISPR-Cas9 editing efficiency enhancer. Repsox invariably increased CRISPR-Cas9 editing in a panel of commonly used cell lines in biomedical research and primary cells. Furthermore, Repsox-mediated editing enhancement in primary human CD4+ T cells enabled the generation of HIV-1-resistant cells with high efficiency. This study demonstrates the potential of transiently targeting cellular pathways by small molecules to improve genome editing for research applications and is expected to benefit gene therapy efforts.